Morbidity pattern of infants in rural Bangladesh - Gazi, Rukhsana; Karim, Fazlul; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2020)
This report is part of a prospective study Investigating the consequences of low birth weight on Infant growth, morbidity and feeding practices in rural Bangladesh. The study registered 644 infants who were followed-up for one year of their age. The study was conducted in three unions of Manikganj district of rural Bangladesh during 1993-1994 to observe the morbidity pattern of infants, assess the treatment pattern for illnesses, and to study the consequence of Low birth weight (LBW) on morbidity during infancy. The overall prevalence of illness was 4.6% among infants aged under 1 year. ARI was most prevalent morbidity among infants under 1 year. An infant suffers from 3-4 episodes of ARI or 2 episodes of diarrhoea or 1 episodes of skin infection during the first year of life. Among infants of 5-12 month old, diarrhoeal disorders (watery, mucoid or bloody type) occurred more frequently comparison to infants of 1-4 months old. Low socioeconomic condition, illiteracy of parents. poor and unhygienic living condition, might be linked with infant morbidity. We found high morbidity prevalence among LBW infants compared to normal or high birth weight infants, but this difference was not statistically significant. Among infants who received any treatment, 71% got allopathic treatment, the main treatment provider being the village doctors. A large proportion of infants did not receive any treatment due to the perception that ··tor mild Illness treatment is not necessary. Community should get health education on prevention, care and danger signs of major illnesses such as ARI and diarrhoea. Provision of sanitary latrines, safe water, and promotion of health education on personal hygiene and environmental sanitation might reduce the risk of morbidity among infants.